Immune tolerance induction using the thyrotropin receptor epitope 78–94 (p37) prevents Graves’ disease in HLA-DR3 transgenic mice - Inaba, Hidefumi; Nonaka, Itsuki; Hashimoto, Daiki; Hirono, Moritoshi; Morita, Shuhei; Kimura, Hiroaki; Iwakura, Hiroshi; Akamizu, Takashi; Nakata, Masanori (Frontiers in Immunology, 2025)
Graves’ disease (GD) is an organ-specific autoimmune thyroid disorder characterized by anti–thyrotropin receptor (TSH-R) antibodies (TRAb), with strong genetic susceptibility conferred by the HLA-DRB1*03:01 (DR3) allele. We investigated whether pre-immunization with the immunodominant TSH-R–derived peptide spanning residues 78–94 (ISRIYVSIDVTLQQLES; p37) could induce immune tolerance and prevent GD in DR3 transgenic mice. GD was induced by intramuscular injection of adenovirus encoding human TSH-R (Ad-TSH-R289). Mice were pretreated with p37 either as a single 50 μg dose or by step-up escalation protocol (0.05 μg, 0.5 μg, and 5 μg), with or without a final 50 μg dose. Ad-TSH-R289 immunization was performed in all groups three weeks after the final peptide administration. While the single-dose protocol failed to prevent disease, the step-up protocol, particularly when including the final 50 μg dose, significantly suppressed serum free thyroxine (FT4) and TRAb levels and prevented histopathological changes in the thyroid gland. These effects were accompanied by an increase in splenic regulatory T cells (CD4+CD25+FoxP3+), a reduction in CD4+PD-1+ T cells, and an increase in CD8+PD-1+ T cells. Depletion of Tregs using an anti-CD25 antibody abrogated the protective effect and elevated serum IFN-γ levels, underscoring the essential role of Tregs in mediating tolerance. In contrast, the weakly immunogenic variant of p37 (37m) provided limited protection, underscoring the necessity of the native peptide sequence. In conclusion, these findings demonstrate that step-up immunization with p37 induces antigen-specific immune tolerance and effectively prevents the development of GD in HLA-DR3 transgenic mice. This strategy represents a promising approach for antigen-specific immunotherapy in autoimmune thyroid disease.